2016
DOI: 10.1002/ps.4335
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of chestnut blight in Croatia: an interaction between host sweet chestnut, its pathogen Cryphonectria parasitica and the biocontrol agent Cryphonectria hypovirus 1

Abstract: Some CHV1 strains belonging to the Italian subtype have similar hypovirulent effects on C. parasitica to those belonging to the French subtype. Furthermore, chestnut susceptibility and recovery could be influenced by the response of chestnut trees to particular hypovirulent C. parasitica isolates, and virus-fungus-chestnut interactions could have significant implications for the success of chestnut blight biocontrol. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…There have been relatively few studies on the impact of CHV‐1 induced hypovirulence using plant material . To our knowledge, this is the first time that the infectivity of virulent and hypovirulent isolates of C. parasitica has been evaluated on chestnut seedlings although other studies have used cut chestnut stems, naturally infected trees or both .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been relatively few studies on the impact of CHV‐1 induced hypovirulence using plant material . To our knowledge, this is the first time that the infectivity of virulent and hypovirulent isolates of C. parasitica has been evaluated on chestnut seedlings although other studies have used cut chestnut stems, naturally infected trees or both .…”
Section: Discussionmentioning
confidence: 99%
“…Following discovery of its biocontrol potential in Italy in the late 1950s, hypovirulence began to be used routinely for disease control . Since then, many studies have identified various mycoviruses that could be useful tools for chestnut blight control in North America such as CHV‐1, CHV‐2, CHV‐3 and CHV‐4 although the latter does not cause hypovirulence, as well as CpMyRV‐1, or CpMyRV2, CHV‐1 and CHV‐2 found in Asia, and CHV‐1 in Europe . Hogan and Griffin showed evidence of the spread of CHV‐1 among local VCGs of the fungus after introduction from Europe into Virginia; and Zamora et al .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations